Association Between the XRCC1, GSTM1, and GSTT1 Polymorphisms in Model of Thyroid Cancer: A Meta-Analysis - Yang, Wenhan; Liu, Wanyu; Zhu, Lei; Lin, Yaqi; Meng, Zilu; Wang, Yudong (Hormone and Metabolic Research, 2023)
Thyroid cancer is the most common malignant tumor of the endocrine system, and its incidence is increasing worldwide each year. This study aimed to explore the association between XRCC1, GSTM1, and GSTT1 polymorphisms in the model of thyroid cancer. The experiment was conducted by searching PubMed, Embase, and Web of Science, with the last search performed in March 2022. A total of 12 studies were included in this meta-analysis, with sample sizes ranging from 211 to 1124. The proportion of XRCC1 polymorphisms (rs25489, GG) in thyroid cancer was slightly lower than that of the normal control group, but the difference was not statistically significant (Mean difference=1.13, 95% CI: 0.99–1.28, p=0.08). The proportion of XRCC1 polymorphisms (rs25489, GA) in thyroid cancer was significantly lower than that of the normal control group (Mean difference=1.32, 95% CI: 1.16–1.52, p<0.00001). The proportion of XRCC1 polymorphisms (rs25489, AA) in thyroid cancer was slightly lower than that of the normal control group, but again, the difference was not statistically significant (Mean difference=0.78, 95% CI: 0.61–1.01, p=0.06). Similarly, the proportion of XRCC1 polymorphisms (rs25487, GG) and (rs25487, GA) in thyroid cancer was lower than that of the normal control group, but the differences were not statistically significant (p=0.22 and p=0.49, respectively). In conclusion, this study found that the proportion of XRCC1 polymorphisms (rs25489, AA) in thyroid cancer was lower than that of the normal control group.
Keywords: XRCC1; GSTM1; GSTT1; thyroid cancer; meta-analysis